2021
DOI: 10.21303/2461-4262.2021.001743
|View full text |Cite
|
Sign up to set email alerts
|

Study on model for cutting force when milling SCM440 steel

Abstract: This article presents empirical study results when milling SCM440 steel. The cutting insert to be used was a TiN coated cutting insert with tool tip radius of 0.5 mm. Experimental process was carried out with 18 experiments according to Box-Behnken matrix, in which cutting speed, feed rate and cutting depth were selected as the input parameters of each experiment. In addition, cutting force was selected as the output parameter. Analysis of experimental results has determined the influence of the input paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…SCM440 steel has been widely used in manufacturing parts with variable loads such as motor drives, gears, plastic injection moulds, rolling shafts and other fields due to its excellent mechanical properties and ability to resist corrosion [1,2]. However, SCM440 steel is classified as difficult-to-machine steel, causing vibrations and rapid tool wear in the machining process [3,4]. SCM440 steel processing shows the effects of different technological parameters on surface quality and vibration [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…SCM440 steel has been widely used in manufacturing parts with variable loads such as motor drives, gears, plastic injection moulds, rolling shafts and other fields due to its excellent mechanical properties and ability to resist corrosion [1,2]. However, SCM440 steel is classified as difficult-to-machine steel, causing vibrations and rapid tool wear in the machining process [3,4]. SCM440 steel processing shows the effects of different technological parameters on surface quality and vibration [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In [10], both the Box-Cox and Johnson transformations were concurrently utilized to refine the accuracy of the cutting force regression model during the milling of SCM440 steel. This investigation further illustrated that employing the Box-Cox transformation facilitated the development of the cutting force regression model with the highest accuracy, followed by the model utilizing the Johnson transformation.…”
Section: Introductionmentioning
confidence: 99%
“…and(10) forms the surface roughness regression model in the case of using the inverse transformation as shown in (13):…”
mentioning
confidence: 99%
“…In [15], it was concluded that the model employing the Johnson transformation had the highest accuracy, whereas the model without data transformation had the lowest one. In [16], both Box-Cox and Johnson transformations were identified to be equally effective in improving the accuracy of cutting force regression models when milling SCM440 steel.…”
Section: Introductionmentioning
confidence: 99%